« Adieu, les résolutions ! » — ou plutôt au revoir et à bientôt La fascination ambiguë de la transgression itérative dans le roman La coscienza di Zeno d’Italo Svevo - Kauß, Anja (Romanica Silesiana)
The article investigates into the conflict of virtue and ‘pleasure principle’ in Italo Svevo’s novel La coscienza di Zeno (1923). Throughout his life, the main character of this novel, Zeno Cosini, sees himself confronted with the demand of leading a virtuous life corresponding to the definition given by his social environment. Engaging himself into this project with resolutions which are equally categorical, firm and ready to be turned round to their opposite, more pleasant side, Zeno Cosini denies his inevitable progression on the slippery slope, his resolutions providing the promising basic condition for his various forbidden pleasures, which at the same time allow him to fathom out the borders and limits of good and evil. The more he digresses from his aim, the more he insists on increasingly exacerbated resolutions, for his emphatic obstinacy concerning his project of being “actively virtuous” allows him to indulge more and more in iteratively “last” deviations from his project which is obviously far beyond his possibilites. Nevertheless, Zeno Cosini manages to wash his hands off by making a virtue out of necessity. Thus, strokes of fate (for instance being diagnosed as having a mortal disease) appear to him as a relief or a blessing, and, looking back, he uses his entire life failure as a shelter from further demands of “reason”. In order to justify (also to himself) his recidivous existence, Zeno Cosini pleads the apparent powerlessness of the modern individual in the face of life which appears to him as per se contingent, ambivalent and full of imponderabilities. He thus delegates the moral responsibility to life itself which he judges to be “original”. From this point of view adapted cynically to his needs, Zeno Cosini realizes that what can be conceived as an “illness” is by no means his vice, his recidivism or his bad conscience, but life itself — which can be catered for with a great deal of good will, analyzed and fathomed out conscientiously via transgression — according to him, is nothing but a manifestation of illness — moreover, an incurable and mortal one — for which there is no remedy, but which can at least be truffled with transgressions. Key words: Transgression, contingency, ambivalence, irony.